A blended learning using contextual teaching learning: strengthening nursing students’ procedural knowledge and interprofessional collaboration - Musrifatul Uliyah; Abdul Aziz Alimul Hidayat; Masunatul Ubudiyah (Jurnal Ners, 2024)
Introduction:The level of knowledge about the types of teaching instruction through blended learning in nursing education is still lacking. This study aims to develop blended learning using contextual learning and evaluate its effect on procedural knowledge and interprofessional collaboration.